1979
DOI: 10.1021/jm00191a027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydroxy- and amino-substituted benzohydroxamic acids: inhibition of ribonucleotide reductase and antitumor activity

Abstract: Benzohydroxamic acids inhibit mammalian ribonucleotide reductase and exhibit antineoplastic activity in L1210 leukemic mice. Five new hydroxy- and amino-substituted benzohydroxamic acids (3,4- and 3,5-OH, 3,4-NH2, 2,3,4- and, 3,4,5-OH) were prepared and tested along with 12 previously reported benzohydroxamic acids (BHA) for enzyme inhibition and antitumor activity. The most potent enzyme inhibitor in this series was 2,3,4-OH-BHA (ID50 = 3.5 microM), which is 140 times more potent than hydroxyurea, but its tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…To date, no serious side effects have been reported with didox treatment even when administered for long periods (21). Didox has been shown to inhibit proliferation of several cancer cell types (18)(19)(20)45) and modulate other cancer chemotherapeutic agents resulting in elevated apoptosis (42). Didox was also shown to synergize with temozolomide in brain tumors and with doxorubicin in liver cancer cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no serious side effects have been reported with didox treatment even when administered for long periods (21). Didox has been shown to inhibit proliferation of several cancer cell types (18)(19)(20)45) and modulate other cancer chemotherapeutic agents resulting in elevated apoptosis (42). Didox was also shown to synergize with temozolomide in brain tumors and with doxorubicin in liver cancer cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…RRM2 is an attractive target for combination therapy, as it is overexpressed in breast cancer and contributes to development of resistance (11). Didox (3,4-dihydroxybenzohydroxamic acid) is a strong inhibitor of ribonucleotide reductase that interferes with DNA synthesis and repair by blocking the production of deoxyribonucleotides and has demonstrated antitumor effects for decades (12,(18)(19)(20). Phase I/II clinical trial studies in patients with cancer showed minimal toxicity and determined that the maximum tolerated dose of didox is 6 g/m 2 , yielding peak plasma levels of 425 mmol/L (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Didox is a polyhydroxysubstituted benzohydroxamic acid derivative that belongs to a new class of RR inhibitors. 34 It has been suggested that didox-induced RR inhibition is due to the reversible destruction of the R2 tyrosil free radical, as demonstrated for hydroxyurea. 11 However, other results suggest that didox has some other properties.…”
Section: Discussionmentioning
confidence: 99%
“…Didox causes greater inhibition of the target enzyme (Elford et al, 1979) and in view of its in vivo activity was entered in phase I evaluation, as part of a co-ordinated programme under the aegis of the Cancer Research Campaign Phase I/II Clinical Trials Committee. It was initially administered by intravenous infusion over 30 min (Veale et al, 1988b).…”
mentioning
confidence: 99%
“…Didox causes greater inhibition of the target enzyme (Elford et al, 1979) Analytical methods Didox levels were measured in plasma and urine by HPLC using a Beckman/Altex IOOA pump and stainless steel column (15 cm x 0.46 cm) packed with a A-Bondapack C18, 10 jim particle size, as previously described (Veale et al, 1988). Metabolites were identified using standards supplied by Elford.…”
mentioning
confidence: 99%